COMPARING EXERCISE PRESCRIPTION METHODS IN KNEE OSTEOARTHRITIS PATIENTS IN MALAYSIA - Gasper, D.D; Bains, B.S; Sadeghi, H; Kumar, P (2018)
This study was a qualitative study that investigated the exercise prescription method in knee osteoarthritis patients in Malaysia. It purposed to fi nd out the most common and effective method used by physiotherapist in prescribing exercises for knee osteoarthritis patients in Malaysia. Method: This study used a self-administered survey questionnaire. The subjects recruited for this study were diagnosed with knee osteoarthritis, age range of between 50 to 80 years old.The methods of delivery were divided into three categories, which include only verbal instructions, verbal instruction together with demonstration and lastly a combination of all three methods including verbal instruction, demonstration and handouts with diagrams. Results: The results showed that 52% received their exercise prescription with verbal instruction and together with demonstration, about 43% of them received all three types of methods which included the verbal instruction, demonstration and take home handouts and 5% of them only received verbal instruction. Out of 5% who received verbal instruction alone, only 1% understood the exercises and the remaining 4% did not and 45% out of 52% who received verbal and demonstration method understood the exercises and the remaining 7% did not. 5% who received only verbal instruction did not seem to continue the exercises at home. 52% received verbal instruction together with demonstration, with about 44% of them having continued their exercises but the remaining 8% did not. 43% who received all three methods reported to continue. Conclusion: The best method of delivering exercises to knee osteoarthritis patients was proven to be the method with a combination of verbal instruction, demonstration together with a take home handout. This method showed very positive outcome and should be implemented and emphasized more in both the government and private sectors of physiotherapy departments